2005
DOI: 10.1590/s0100-39842005000300004
|View full text |Cite
|
Sign up to set email alerts
|

Fontes utilizadas pelas mulheres para aquisição de conhecimentos sobre câncer de mama

Abstract: OBJETIVO: Identificar as principais fontes utilizadas pelas mulheres para adquirir informações sobre câncer de mama; determinar se existe associação entre as fontes de informação usadas e o nível de escolaridade e renda familiar; estabelecer como as mulheres avaliam seus próprios conhecimentos sobre câncer de mama (auto-avaliação); determinar se esta auto-avaliação tem efeito sobre os hábitos referidos da prática do auto-exame das mamas. MATERIAIS E MÉTODOS: Quinhentas e trinta e uma mulheres, com idade de 20 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
4

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 17 publications
(9 reference statements)
0
7
0
4
Order By: Relevance
“…Essa orientação foi individual (33,33%) ou em consultas em que eram acompanhantes (12,5%). O médico, assim como todos os profissionais de saúde, é um importante agente disseminador de informações sobre câncer de mama, por isso é essencial que se mantenham familiarizados com as recomendações e métodos disponíveis para prevenção do câncer de mama, para estimularem as mulheres ao autocuidado (16) .…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Essa orientação foi individual (33,33%) ou em consultas em que eram acompanhantes (12,5%). O médico, assim como todos os profissionais de saúde, é um importante agente disseminador de informações sobre câncer de mama, por isso é essencial que se mantenham familiarizados com as recomendações e métodos disponíveis para prevenção do câncer de mama, para estimularem as mulheres ao autocuidado (16) .…”
Section: Resultsunclassified
“…Dos meios de comunicação, a mídia/TV (20,83%) foi a mais citada para obtenção de informação quanto à prevenção do câncer de mama; dados coincidentes com outros estudos referem que "a TV tem um grande poder de penetração em todas as camadas sociais, sugerindo que as campanhas de combate ao câncer de mama devem necessariamente usar este instrumento de comunicação como elemento veiculador" (16) .…”
Section: Resultsunclassified
“…We believe that the mentioning of this methodby so many participantsis possibly due to the previous media campaigns on health where this method was mentioned as fundamental for the early detection of breast cancer. Studies have shown that the media is an important means of communication for dispensing knowledge on breast cancer 15 irrespective of a person's level of education or income 16 . The ECM that is carried out by health care professionals is a simple and non-invasive method without costs with a sensibility rate of 94.5% and specificity rate of 87.7% 17 .…”
Section: Discussionmentioning
confidence: 99%
“…12 In this sense, it is important to think about the need for a multidisciplinary team, that is, the doctor 13 is not the only one to talk to the patient and family in the sense of answering questions about the disease, about the course of treatment and prognosis; the lack of clarity of such information may cause distress, refused treatment, morbidity increase, among other health problems.…”
Section: Discussionmentioning
confidence: 99%
“…13 On the other hand, this kind of communication related to health can cause viewers to receive improper or inadequate information without a critical analysis -being open to interpretation that may result in risks to the health of patients with certain diseases.…”
Section: Discussionmentioning
confidence: 99%